Changes in Menstrual Pain Following Dysmenorrhea Exercise among Early-Adolescent Female Students at Two Elementary Schools: A One Group Pretest–Posttest Study - Bunga Romadhona Haque; Yenny Retno Kinasih; Synthia Anggarini (Journal of Health and Nutrition Research, 2026)
Dysmenorrhea is a menstrual complaint among adolescent girls and may interfere with activities, school attendance, concentration, and academic performance. Dysmenorrhea exercise is a nonpharmacological approach that may support menstrual pain management. This study assessed changes in menstrual pain following a dysmenorrhea exercise program among early-adolescent female students at SDN 18 Kramat Jati, East Jakarta, and SDN Pengadilan 5 Bogor. A quantitative preexperimental study with a one-group pretest–posttest design was conducted from November to December 2025. Participants were selected using purposive sampling. A total of 106 female students aged 10 to 12 years who had experienced menarche and reported menstrual pain participated. The intervention consisted of dysmenorrhea exercise four times per week for three weeks, with each session lasting 30 minutes. Menstrual pain intensity was assessed before and after the intervention using the Numeric Rating Scale. Differences in preintervention and postintervention scores were analyzed using the Wilcoxon signed-rank test. At SDN 18 Kramat Jati, the mean pain score decreased from 6.85 ± 0.62 to 2.75 ± 0.55, corresponding to a mean change of 4.10 points. At SDN Pengadilan 5 Bogor, the mean score decreased from 7.01 ± 0.44 to 2.68 ± 0.49, corresponding to a mean change of 4.33 points. Postintervention scores were significantly lower than preintervention scores in the overall sample (p < 0.001). Lower pain scores were observed at both study sites. Dysmenorrhea exercise may be a useful, simple, low-cost, school-based self-care strategy, although the findings should be interpreted cautiously because the study did not include a control group.